Evaluation Of Management Of Capitation Funds - Rachmawati, Amalia; Syaodih, Erliany; Widjaja, Yani Restiani (JKM (Jurnal Kebidanan Malahayati), 2024)
Universal Health Coverage (UHC) adalah program yang menjamin setiap manusia mendapatkan akses pelayanan kesehatan tanpa menimbulkan kerugian finansial penggunanya. Indonesia menerapkan UHC dengan Jaminan Kesehatan Nasional (JKN). Pelayanan kesehatan di tingkat primer diberikan oleh FKTP. Sistem pembayaran JKN pada FKTP oleh BPJS Kesehatan adalah dengan sistem kapitasi. Klinik Pratama Albar adalah FKTP di Kabupaten Bandung yang melayani peserta JKN dan mengelola dana kapitasi. Adanya peningkatan jumlah kapitasi terdaftar, kenaikan tarif kapitasi, dan kunjungan pasien belum sejalan dengan peningkatan laba dan pemanfaatan dana kapitasi yang ada sehingga diperlukan adanya evaluasi manajemen keuangan klinik dalam mengelola dana kapitasi. Tujuan penelitian ini adalah mengevaluasi pengelolaan dana kapitasi Klinik Pratama Albar dalam penganggaran dan pemanfaatannya. Penelitian ini adalah deskriptif kualitatif dengan metode observasi, wawancara, dokumentasi, dan triangulasi. Hasil penelitian menunjukkan kerjasama Klinik Pratama Albar dan BPJS Kesehatan berlangsung satu arah dan proses pencairan dana kapitasi berlangsung lancar. Klinik Pratama Albar telah memiliki struktur manajemen dan alur keuangan, namun belum dilakukan perencanaan anggaran yang baik. Dana kapitasi adalah sumber pemasukan terbesar klinik mencapai 86% dan pemanfaatannya untuk gaji staff dan biaya operasional dengan proporsi 59:41. Penelitian ini menyimpulkan bahwa pentingnya evaluasi pengelolaan dana kapitasi untuk menyusun strategi pengembangan klinik. Kata Kunci : Klinik Pratama, Dana Kapitasi, Evaluasi Manajemen Keuangan ABSTRACT Universal Health Coverage (UHC) is a program that ensures every human being gets access to health services without causing financial losses to its users . Indonesia implements UHC with the National Health Insurance (JKN) . Health services at the primary level are provided by FKTP . The JKN payment system at FKTP by BPJS Health is with a capitation system. Klinik Pratama Albar is an FKTP in Bandung Regency that serves JKN participants and manages capitation funds. The increase in the number of registered capitations, the increase in capitation rates, and patient visits have not been in line with the increase in profits and the utilization of existing capitation funds, so it is necessary to evaluate the clinic's financial management in managing capitation funds . The purpose of this study is to evaluate the management of capitation funds of the Klinik Pratama Albar in budgeting and its utilization. This research is qualitative descriptive with observation, interviews, documentation, and triangulation methods. The results of the study showed that the collaboration between the Klinik Pratama Albar and BPJS Health took place in one direction and the process of disbursing capitation funds went smoothly. Albar Pratama Clinic already has a management structure and financial flow, but good budget planning has not been carried out. The capitation fund is the largest source of income for clinics reaching 86% and its utilization is for staff salaries and operational costs with a ratio of 59:41. This study concludes that the importance of evaluating capitation fund management to develop a clinic development strategy. Keywords : Primary Clinic, Capitation Fund, Financial Management Evaluation Afifah, LAN, Arso, SP, Fatmasari, EY (2019). Analysis of Capitation Fund Management Mechanism at Primary Clinic in Pedurungan District, Semarang City. Public Health Journal (e-Journal) , 7(4), 683-694.Agustina, A., Hidayat, B., Pandujiwo N. (2021). Systematic Review: Development of Risk-Adjusted Capitation Payment System in Various Countries. Indonesian Journal of Health Economics . 6, (2), 81-94.Agustina, R., Dartanto, T., et al. (2019). Universal Health Coverage in Indonesia: Concept, Progress, and Challenges. The Lancet . 393, P75-102.Amalia. (2024). Getting to Know Clinical Management: Strategies and Goals. https://medminutes.io/mengenal-manajemen-klinik-strategi-dan-wenangnya/Ardhiasti, A., Setiawan, ER (2021). Performance-Based Capitation Payments at Primary Health Facilities (FKTP) in Malang City. Journal of Health Education , 10(2), 208 – 225.Aryani, AD (2022) . Factors Affecting the Achievements of Performance-Based Capitation: A Scoping Review. National Health Insurance Journal (JJKN) , 2(1), 53-65.Central Bureau of Statistics. (2023). Health Statistics Profile 2023. Jakarta: Central Statistics Agency.Buana, T. (2023). Gaps in Health Services. https://www.academia.edu/108803827/Kesengap_Dalam_Pelayanan_Kesehatan?sm=aDekrita., Andria, Y., and Samosir, M. (2022) . Hospital Financial Management Concept and Analysis .Pekalongan: PT. Nasya Expanding Management.rika, K. (2020). Study of Islamic Economics in the Implementation of Health Insurance at the First Health Facility of BPJS Health Center Palasari Subang Service. EKSISBANK Islamic Economics and Banking Business, 4(2), 201-213. DOI: https://doi.org/10.37726/ee.v4i2.133Geodesy, M., Wardani2, R. (2022). Performance of Health Facilities in Relation to Capitation Payments. The International Virtual Conference on Nursing, KnE Life Sciences , 766–778. DOI 10.18502/kls.v7i2.10377Giovanella, L., Machado, CV, et all. (2018). Universal Health System and Universal Health Coverage: Assumptions and Strategies. Ciencia and Saude Colectiva , 23(6), 1763-1776. https://pubmed.ncbi.nlm.nih.gov/29972485/Hasan, S., Elpisah, E., Sabtohadi, J., Nurwahidah, M., Abdullah, A., & Fachrurazi, F. (2022). Financial Management. Widina Publisher. The Importance of Financial Management in Clinical Management (medminutes.io )Herawati, A. (2023). How to Evaluate a Company's Financial Performance?. How to Evaluate a Company's Financial Performance? (kledo.com)Juwita, NE, Santoso, D. (2023). Analysis of Effective Communication on Performance-Based Capitation Achievement in Primary Health Facilities in Bengkayang Regency. National Health Insurance Journal (JJKN) , 3(2), 37-55. https://jurnal-jkn.bpjs-kesehatan.go.id/index.php/jjkn/article/view/175/98Ministry of Health of the Republic of Indonesia. (2016). National Health Insurance (JKN) Guidebook for Key Populations . Jakarta: Ministry of Health of the Republic of Indonesia.Ministry of Health of the Republic of Indonesia. (2023). Indonesian Health Profile 2022. Jakarta: Ministry of Health of the Republic of Indonesia.Albar Primary Clinic. (2023). Profile of Albar Primary Clinic . Bandung: Albar Primary Clinic.Koohpayehzadeh, J., et al. (2021). "Best Practices in Achieving Universal Health Coverage: A Scoping Review".Medical Journal of the Islamic Republic of Iran (MJIRI). 35, 191.Kurniawan, MF, Siswoyo, BO, Mansur, F., et al. (2016). Management and Utilization of Capitation Funds (Monitoring and Evaluation of National Health Insurance in Indonesia). Indonesian Journal of Health Policy , 5 (3), 122-131.Lubis, YM, Syahiza, R. (2021). JKN – KIS Participant Services During the Pandemic at BPJS Kesehatan. PRAJA Observer: Journal of Public Administration Research, 1(4), 35-39.Mota, E.C., Shofiana, J., & Kurniawati, A.N. (2020). JKN Financing Management. Ahmad Dahlan University . https://www.academia.edu/43644444/Manajemen_Pembiayaan_JKNMulya, AG (2023). Social Security Administering Body (BPJS) Health as a Social Justice-Based Management Strategy in Health Services. https://www.academia.edu/108832339/Badan_Penyelenggara_Jaminan_Sosial_BPJS_Kesehatan_sebagai_Strategi_Manajemen_Berbasis_Keadilan_Sosial_dalam_Pelayanan_Kesehatan?sm=aNasution, NM, Lestari, R., Saphira, SJ, & Gurning, FP (2023). Analysis of JKN Capitation Fund Management at Primary Health Facilities (FKTP) in Medan City. INNOVATIVE: Journal Of Social Science Research , 3(3), 7953-7960. https://j-innovative.org/index.php/InnovativeNowicki, M. (2018). Introduction to The Financial Management of Healthcare Organizations . Chicago: American College of Healthcare Executives.Nurfikri, A. (2021). Analysis of the Readiness of the Muhammadiyah Cirebon Primary Clinic in Facing Performance-Based Capacitance Payments. Indonesian Health Policy Journal: JKKI, 10(3), 151-157.Nurvita, S. (2021). JKN Participant Services During the Pandemic. JURMIK (Journal of Medical Records and Health Information Management) , 1(2), 19-23.Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2023 concerning Standard Tariffs for Health Services in the Implementation of the Health Insurance Program.Puteri, DA, Syaodih,, E., Agung, IWP, Andikarya, O. (2024). The Influence of Health Service Quality on the Interest in Repeat Visits of BPJS Patients at Kirana Medika Clinic Bandung. Journal of Hospital Management, 2(1), 13-23.Putri, AE (2014). Understanding JKN National Health Insurance . Jakarta: Friedrich-Ebert-Stiftung Indonesian Representative OfficeRachmawati, A., Ranggelika, I., Kholidianti, QE, et al. (2024). Implementation and Evaluation of the Albar Pratama Clinic Management Information System ( Assist ). Journal of Social and Economics Research, 6(1), 644-650. https://doi.org/10.54783/jser.v6i1.394Rahayu, TW, Rahim, AH, & Suwarsi, S. (2022). SWOT Canvas business model for hospitals . Bandung: UNISBA Scientific Publication Unit.Rahim, AH, & Raksanagara, A. (2022). Introduction to epidemiology . Bandung: UNISBA Scientific Publication Unit.Ridho, F., Soebyakto, BB, & Idris, H. (2020). The Analysis of Management and Utilization of Capitation Fund for Dentistsin Palembang and Lubuklinggau. The Indonesian Journal of Public Health , 15(2), 162-172 .Roekminiati, S., Pramono, S., Sholichah, N., & Pramudiana, ID (20 19). Implementation of The JKN Programs on The Community Health Center at Level 1. EAI European Union Digital Library , 2019-09-30. https://eudl.eu/doi/10.4108/eai.30-7-2019.2287604Rohrohmana, EM, Noviana, F., Purwadhi., Widjaja, YR (2024). Strategy for Developing a Clinic into a Hospital: Literature Review. Journal of Innovation Research and Knowledge (JIRK) , 4(4), 2329-2336.Sandra, C., Herawati, YT, Baroya, N., et al. (2021). Implementation of Commitment-Based Capitation Payment Policy (KBKP) in Jember Regency. Ikesma: Journal of Public Health Sciences, 17(1), 52-58. DOI: 10.19184/ikesma.v17i1.22441Sari, DP, Rahayu, S., & Yudi. (2020). The Concept of National Health Insurance Fund Management Based on Nosarara Nosabatutu. Multiparadigma Accounting Journal , 11(1), 89-108. https://repository.unja.ac.id/21595/Setiawan, NH, Syaodih, E., Hidayat, D., Noor, CM (2023) . Clinic Marketing Strategy in Increasing the Number of Patient Visits. e-Proceedings of the ARS University Master of Management, 1(1), 78-84.Supartika, EY, Kosasih, Asnar, ESM, (2024). Strategy to Increase the Achievement of Performance-Based Capitation Indicators Through Management Functions at Health Centers in West Bandung Regency. Open Journal Systems, 18(10), 2553-2566.(2018). Hospital financial management, Concept and Analysis . Bandung: PT Refika Aditama.Thabroni, G. (2022). Financial Management: Definition, Function, Objectives & Scope. https://serupa.id/manajemen-keuangan-pengertian-fungsi-utama-ruang-lingkup/    WHO, Universal Health Coverage . 2023